2021
DOI: 10.1371/journal.pmed.1003097
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic capacity and its associations with incident dependence and mortality in 10/66 Dementia Research Group studies in Latin America, India, and China: A population-based cohort study

Abstract: Background The World Health Organization (WHO) has reframed health and healthcare for older people around achieving the goal of healthy ageing. The recent WHO Integrated Care for Older People (ICOPE) guidelines focus on maintaining intrinsic capacity, i.e., addressing declines in neuromusculoskeletal, vitality, sensory, cognitive, psychological, and continence domains, aiming to prevent or delay the onset of dependence. The target group with 1 or more declines in intrinsic capacity (DICs) is broad, and impleme… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(39 citation statements)
references
References 47 publications
5
34
0
Order By: Relevance
“…Secondly, the study specifically explored the impact of lifestyle behaviours on IC. Only a few studies are available examining the association of lifestyle factors with IC [ 14 , 23 , 67 ]. Thirdly, the study carefully accounted for the impact of maximum potential confounders, including work participation and place of residence, which are ignored in most of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, the study specifically explored the impact of lifestyle behaviours on IC. Only a few studies are available examining the association of lifestyle factors with IC [ 14 , 23 , 67 ]. Thirdly, the study carefully accounted for the impact of maximum potential confounders, including work participation and place of residence, which are ignored in most of the studies.…”
Section: Discussionmentioning
confidence: 99%
“…IC is defined as the set of physical and mental capacities of an individual covering five domains, namely, locomotion, cognition, sensory, vitality, and psychological domains. Previous studies showed that the domains of IC (3)(4)(5)(6)(7) as well as the total score of all domains (5,6) were associated with self-care, frailty, living dependency, hospitalization, and mortality among the older population. These findings not only highlighted the importance of IC as a useful tool to detect, prevent, and delay the onset of disabilities but also accelerated the shift from a disease-based approach to a person-centered approach in clinical practice.…”
Section: Introductionmentioning
confidence: 98%
“…16 In another study by Martin et al, they demonstrated that decline in intrinsic capacity was significant with increased age and those with decreased IC had substantially increased risks of dependence and death. 17…”
Section: Discussionmentioning
confidence: 99%